Influences of Wall Angle on Forming Forces in Single-Point Incremental Forming - Ho, Ky-Thanh; Nguyen, Duc-Hoa; Giang, Quyet-Thang (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
This study presents experimental results evaluating the influence of wall angle on the forming process of AA5052 aluminum alloy sheets using the incremental sheet forming process. The wall angle investigated varied within the range of 45°-50°-55°-60°, with step-down sizes chosen as 0.5mm and 1.0mm. The forming process was conducted under lubrication conditions, with other parameters remaining constant, including a feed rate of 2400 mm/min, a forming depth of 30mm, a non-rotating tool configuration, and a spatial screw trajectory. The analysis of forming forces showed that the process underwent three distinct stages and reached a stable state when the main forming force, Fz, attained its peak value. Additionally, as the forming angle increased, all forming force components exhibited a corresponding increase. The results indicated that at a forming angle of 60°, the process was unsuccessful for both step-down sizes, as the excessive thinning of the sheet led to material failure. The results also showed that as the step-down size increased, surface waviness became more pronounced.